Influence of stance width and binding angles on tibial rotation and ollie jump height in snowboarding - List, R.; Bründler, J.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the influence of stance width and binding angles on tibial rotation during a flat landing of a drop jump and Ollie jump height in snowboarders. Six binding conditions combined of three stance widths and two binding angle setups (forward and duck stance) were tested on 10 expert freestyle snowboarders. Relating to knee injury risk, tibial rotation was assessed using skin markers during the flat landing of a 51cm drop jump. The influence on the performance was investigated by the assessment of the Ollie jump height using a Quattro Jump force plate. An influence of the binding parameters on tibial rotation during a flat landing was found, whereas Ollie jump height didn`t differ significantly. A bigger angle of the front foot and a negative angle of the rear foot reduced the magnitude of internal tibial rotation.